What We Choose to Remember: Imagined Shared Narratives of Education During COVID-19 - Hewitt, Kimberly Kappler; Carlone, Heidi; Faircloth, Beverly S.; Gonzalez, Laura M.; He, Ye; Vetter, Amy (Journal of Interdisciplinary Studies in Education, 2021)
The impacts of the COVID-19 pandemic on educational policies and practices are unprecedented. With the majority of educational institutions forced to limit face-to-face interactions, teaching and learning have rapidly taken on vastly new meanings. Even in the midst of the uncertainties of this pandemic, predictions for the post COVID-19 world have begun to emerge (e.g., Karlgaard, 2020; Kim, 2020). Yet as we move forward, we collectively create the past. That is, historical implications are never objective descriptions of what occurred, but rather collective decisions about how we choose to remember the past (Anderson, 1991; Breuilly, 2016). In this spirit, we ask: As educators imagining education in 2030, through the lens of our COVID-19 experience, what will we choose to remember and what generative impact do we want to take pride in claiming?